Effects of acute N-acetylcysteine challenge on cortical glutathione and glutamate in schizophrenia: A pilot in vivo proton magnetic resonance spectroscopy study. (May 2019) - Girgis, Ragy R.; Baker, Seth; Mao, Xiangling; Gil, Roberto; Javitt, Daniel C.; Kantrowitz, Joshua T.; Gu, Meng; Spielman, Daniel M.; Ojeil, Najate; Xu, Xiaoyan; Abi-Dargham, Anissa; Shungu, Dikoma C.; et al.
Highlights: We observed no differences in mPFC glu and dACC GSH and glu at baseline. We observed no differences in mPFC glu and dACC GSH and glu after NAC challenge. Glu and glx correlated significantly in both dACC ( r = 0.53, p = 0.02) and mPFC ( r = 0.65, p = 0.006) in control subjects, but only in dACC in patients ( r = 0.67, p = 0.002; mPFC r = 0.07, p = 0.8). Abstract: Findings from in vivo brain proton magnetic resonance spectroscopy ( 1 H MRS) and preclinical studies have suggested region- and medication status-dependent increases in glutamate (Glu) levels and deficiencies in glutathione (GSH) levels in schizophrenia. N-acetylcysteine (NAC), a GSH synthesis precursor, has demonstrated modest clinical benefit in schizophrenia. The objective of this study was to examine the effects of acute administration of NAC on GSH and Glu levels measured with 1 H MRS in 19 patients with schizophrenia and 20 healthy control subjects. Levels of GSH were acquired in dorsal anterior cingulate cortex (dACC), and those of Glu in dACC and medial prefrontal cortex (mPFC), at baseline and 60 min following acute oral administration of 2400 mg of NAC. No differences in the levels of GSH or Glu were found at baseline or following NAC administration between patients with schizophrenia and control subjects in either of the targeted brain regions. Future studies measuring GSH levels in brain regions previously found to exhibit glutamatergic abnormalities or using genetic polymorphisms, while controlling for the age and medication status of the cohorts, are warranted to better identify groups of patients more likely to respond to NAC and its mode of action and mechanisms.